Medium and long-term radiographic and clinical outcomes of Dynesys dynamic stabilization versus instrumented fusion for degenerative lumbar spine diseases - Lu-Ping Zhou; Ren-Jie Zhang; Jia-Qi Wang; Hua-Qing Zhang; Jin Shang; Yang Gao; Chong-Yu Jia; Jing-Yu Ding; Lai Zhang; Cai-Liang Shen (BMC Surgery, 2023)
Abstract Background Dynesys stabilization (DS) is utilized to preserve mobility at the instrumental segments and prevent adjacent segment pathology in clinical practice. However, the advantages of DS method in medium and long-term follow-up remain controversial. Objective To compare the radiographic and clinical outcomes between DS and instrumented fusion in the treatment of degenerative lumbar spine disease with or without grade I spondylolisthesis with a minimum follow-up period of 2 years. Methods We conducted a comprehensive search of PubMed, EMBASE, Cochrane, and Web of Science databases, Chinese National Knowledge Databases, and Wanfang Database for potentially eligible articles. Clinical outcomes were assessed in terms of VAS and ODI scores, screw loosening and breakage, and surgical revision. Radiographic outcomes were assessed in terms of postoperative range of movement (ROM) and disc heigh. Moreover, adjacent segment degeneration (ASDeg) and adjacent segment disease (ASDis) were evaluated. Results Seventeen studies with 1296 patients were included in the meta-analysis. The DS group was associated with significantly lower postoperative VAS scores for low-back and leg pain, and lower rate of surgical revision than the fusion group. Moreover, the Dynesys group showed significantly less ASDeg than the fusion group but showed no significant advantage over the fusion group in terms of preventing ASDis. Additionally, the ROM at the stabilized segments of the fusion group decreased significantly and that at the adjacent segments increased significantly compared with those of the DS group. Conclusion DS showed comparable clinical outcomes and provided benefits in preserving the motion at the stabilized segments, thus limiting the hypermobility at the adjacent segments and preventing ASDeg compared with the fusion method in degenerative disease with or without grade I spondylolisthesis.